Alumina-zirconia eutectic sintering material and preparation method thereof

By using alumina-zirconia eutectic sintering materials and spark plasma sintering technology, the problems of strength decay and adhesion of alumina-zirconia composite ceramic materials during high-temperature service have been solved, resulting in eutectic ceramic materials with high density and excellent mechanical properties, suitable for the field of high-temperature structural ceramics.

CN120841941APending Publication Date: 2025-10-28ANHUI JINHETAI NEW MATERIALS CO LTD

Patent Information

Application Number
CN202511019761.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-23
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing alumina-zirconia composite ceramic materials have problems such as grain coarsening leading to strength attenuation during high-temperature service, easy adhesion when in contact with zirconium-containing ceramic bodies, random distribution of zirconia phases lacking effective structural design, insignificant toughening effect, low flexural strength, high cost, and unsuitability for large-scale industrial production.

Method used

By using alumina-zirconia eutectic sintering material, the morphology of the eutectic structure is controlled by yttrium oxide, and by combining it with spark plasma sintering technology, the morphology and distribution of alumina and zirconia grains are controlled to form a layered interlocking structure, thereby achieving high density and excellent mechanical properties.

Benefits of technology

The prepared alumina-zirconia eutectic sintered material has high density, excellent flexural strength and fracture toughness, and is suitable for the field of high-temperature structural ceramics. It is low in cost, simple in process, and suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120841941A_ABST
    Figure CN120841941A_ABST
Patent Text Reader

Abstract

The invention relates to an alumina-zirconia eutectic sintering material and a preparation method thereof, and relates to the technical field of high-temperature structural ceramic materials. The preparation method comprises the following steps: dispersing 80-95 parts of aluminum oxide powder, 1-10 parts of zirconium oxide powder and 0.1-1 part of yttrium oxide powder in a solvent, and carrying out wet grinding and drying to obtain mixed powder; and adding 1-3 parts of a binder into the mixed powder, uniformly grinding, drying, carrying out compression molding, and carrying out SPS (spark plasma sintering) treatment to obtain the alumina-zirconia eutectic sintering material. The alumina-zirconia eutectic sintering material is obtained through raw material powder wet grinding, compact preparation and spark plasma sintering. The eutectic sintering material has the characteristics of high strength, high fracture toughness, good creep resistance and the like; the method is simple and easy to operate, green and environment-friendly, low in cost, short in process, high in efficiency and beneficial to industrial large-scale production and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of high-temperature structural ceramic materials, and in particular to an alumina-zirconia eutectic sintering material and its preparation method. Background Technology

[0002] Alumina-based sintering supports are structural components widely used in the sintering process of high-end ceramic products (such as electronic ceramics and structural ceramics), and are crucial for supporting the development of my country's high-tech industries. Traditional alumina-based sintering supports face two major technical bottlenecks: first, grain coarsening during long-term high-temperature service leads to strength degradation; second, the formation of low-melting-point eutectic compounds upon contact with zirconium-containing ceramic blanks causes adhesion. Although existing research has improved performance by adding additives such as magnesium oxide and yttrium oxide, the core issues of eutectic phase regulation and interfacial reaction control have not been fundamentally resolved.

[0003] Alumina-zirconia composite ceramics are ideal for preparing high-performance sintering materials due to their excellent high-temperature mechanical properties and chemical stability. However, existing research mainly focuses on dispersed phase toughening (such as alumina reinforced by zirconia particles), with limited research on the design of eutectic ceramic microstructures and their application in sintering. The microstructures of each phase in the prepared sintering ceramic materials do not achieve the maximum toughening effect, thus failing to meet the requirements for long service life. By controlling the eutectic microstructure, the synergistic optimization of high strength and low interfacial reactivity in the sintering material can be achieved, providing an innovative direction for this invention.

[0004] Chinese patents CN115536371A and CN119390466A disclose two methods for preparing high-strength alumina ceramics. The core idea is to add appropriate amounts of SiO2, MgO, and CaO as sintering aids to the α-Al2O3 component, or to add silicon carbide whiskers to improve the sintering degree or toughness of the alumina ceramic. However, the addition of various sintering aids is detrimental to the high-temperature performance of alumina ceramics and worsens their creep performance during high-temperature service. While adding one-dimensional micro / nanomaterials such as silicon carbide whiskers as the main means of toughening ceramic fibers still suffers from problems such as uneven dispersion during preparation and oxidation of silicon carbide whiskers during service. Therefore, the mechanical properties of the prepared alumina-based ceramic materials still cannot meet service requirements.

[0005] Chinese patents CN103072325A and CN118515471A disclose two types of high-strength alumina-zirconia multiphase ceramics and their preparation methods. These methods toughen alumina-based ceramic materials by introducing tetragonal zirconia and achieve a micro-nano composite structure. Essentially, they utilize the phase transformation of tetragonal zirconia to strengthen the ceramic matrix composite material. However, the zirconia phase in these ceramic matrix composites is randomly distributed and lacks an effective crystal structure design, resulting in a relatively limited toughening effect from the zirconia phase transformation.

[0006] Chinese patent CN112456979A discloses a method for preparing zirconia-toughened alumina powder. The method involves mixing aluminum nitrate solution and zirconium nitrate solution twice, then adding an alkaline aqueous solution to obtain a precipitate mixture, and finally calcining and spray granulating to obtain zirconia-toughened alumina powder. After pressing and air sintering, ceramics are obtained. Obviously, the flexural strength of the ceramic is low, the powder preparation process is complex, the operation is difficult, and the cost is high.

[0007] Chinese patent CN106518028A discloses a method for preparing micro / nano zirconia / alumina composite materials. This method involves first cold isostatically pressing an appropriate amount of submicron-sized ZrO2 powder, then sintering it to a semi-cooked state. Next, Al2O3 powder is added to the semi-cooked ZrO2 balls and wet-milled. After drying, Al2O3 powder is added again for further milling. Finally, a binder is added, and the mixture is ground, dry-pressed, cold isostatically pressed, de-plasticized, and sintered. The preparation method is complex, lengthy, and costly. The ZrO2 grains are randomly distributed within the Al2O3 matrix, and their morphology is identical to the initial state, making it difficult for the dispersed ZrO2 grains in the Al2O3 matrix to achieve the maximum toughening effect. Summary of the Invention

[0008] To address the technical problems in the preparation of alumina-zirconia composite ceramic materials in existing technologies, such as the deterioration of high-temperature creep performance due to the addition of various sintering aids, the random distribution of the zirconia phase without effective crystal structure design, insignificant toughening effect, low flexural strength, low efficiency, high cost, and unsuitability for large-scale industrial production, this invention proposes an alumina-zirconia eutectic sintering material and its preparation method that can solve the aforementioned technical problems. The technical solution is as follows:

[0009] An alumina-zirconia eutectic sintering material, comprising 80-95 parts alumina powder, 1-10 parts zirconia powder, 0.1-1 parts yttrium oxide powder, and 2-5 parts binder.

[0010] Optionally, the microstructure of the alumina-zirconia eutectic sintered material is characterized by alternating layers of alumina and zirconia grains, with zirconia grains randomly interspersed in stripe or cylindrical rod shapes within the alumina grains. The grain thickness is <200 nm, the alumina grain size is 100-1000 nm, and the Y₂O₃ grain size is 100-5000 nm. 2 Within the area, the number of alumina grains is 100-2000, and the number of zirconia grains is 10-500.

[0011] Optionally, the alumina-zirconia eutectic sintered material has a density of 92-97%, a microhardness of 16-21 GPa, a flexural strength of 820-980 MPa, a thermal conductivity of 4.0-9.0 W / m·K, and a coefficient of thermal expansion of 7.0-8.5 × 10⁻⁶. -6 / K, fracture toughness is 6.6-8.9 MPa·m 1 / 2 The maximum operating temperature is 1800-2000℃, and the compression creep is 0.01-0.03% under the conditions of 1200℃, 100MPa and heat preservation and pressure holding for 600min.

[0012] A method for preparing the alumina-zirconia eutectic sintering material, wherein the preparation method of the alumina-zirconia eutectic sintering material specifically includes the following steps:

[0013] S1. Wet milling of raw material powder: Alumina powder, zirconium oxide powder, and yttrium oxide powder are dispersed in a solvent in the required proportion of alumina-zirconia eutectic sintering material, and then wet milled and dried to obtain mixed powder;

[0014] S2, Preparation of compact: Add binder to the mixed powder of S1 and grind it evenly. After drying, press it into shape to obtain the mixed compact;

[0015] S3, Spark Plasma Sintering: The mixed compact of S3 is subjected to SPS spark plasma sintering to obtain alumina-zirconia eutectic sintering material.

[0016] Optionally, the alumina powder of S1 has a particle size of 0.5-10 μm and a purity of Al2O3≥99wt%; the zirconium oxide powder has a diameter of 1-5 μm and a purity of ZrO2≥99wt%; and the yttrium oxide powder has a diameter of 0.1-0.5 μm and a purity of Y2O3≥99wt%.

[0017] Optionally, the solvent of S1 is one or more of deionized water and anhydrous ethanol, the grinding balls for wet milling are alumina balls, the ball-to-material ratio is 1:2.0-1:3.0, the ball milling speed is 300-400 r / min, the ball milling time is 24-36 h, the drying temperature is 50-110 ℃, the drying time is 24-36 h, and the average particle size of the mixed powder is 0.1-5 μm.

[0018] Optionally, the binder of S2 is one or more aqueous solutions of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, and carrageenan, and the organic content is 5 wt%.

[0019] Optionally, the grinding media for S2 with added binder is alumina balls, the grinding speed is 300-400 r / min, the drying temperature is 50-110℃, the drying time is 24-36 h, and the molding pressure for pressing is 100-150 MPa.

[0020] Optionally, the pressure on the blank during the SPS discharge plasma heat treatment process of S3 is 5-20kN, the heating rate during sintering is 50-100℃ / min, the cooling rate is 100-200℃ / min, the sintering atmosphere is argon atmosphere, the heat treatment temperature is 1500-1700℃, and the holding time is 2-10min.

[0021] Technical principle of the invention:

[0022] Eutectic ceramics possess characteristics such as interphase coupling growth, interwoven mosaic structure, pure interphase interfaces, and the absence of amorphous structures. They exhibit excellent mechanical properties and creep resistance under high-temperature conditions, attracting widespread attention in recent years. Currently, common methods for preparing eutectic ceramics include laser rapid solidification, directional solidification, and high-gravity casting. However, there is an urgent need to develop more convenient sintering techniques for preparing eutectic ceramics to meet the application needs of sintered materials.

[0023] The main toughening method for current alumina-zirconia ceramic materials is to introduce a zirconia phase and utilize the microcracks generated by phase transformation during sintering to achieve toughening. However, when zirconia is added as a second phase to alumina-based ceramic materials, its random distribution and the difficulty in controlling and designing its crystal microstructure through direct introduction result in a relatively limited toughening effect.

[0024] The above technical solution has at least the following advantages compared with the existing technology:

[0025] The above-mentioned solution proposes an alumina-zirconia eutectic sintering material and its preparation method, which can solve the technical problems existing in the preparation of alumina-zirconia composite ceramic materials, such as the deterioration of high-temperature creep performance due to the addition of various sintering aids, the random distribution of zirconia phase without effective crystal structure distribution design, the insignificant toughening effect, the low flexural strength of composite ceramic materials, low efficiency, high cost, and unsuitability for large-scale industrial production.

[0026] This invention employs spark plasma sintering technology to rapidly raise the temperature to the target temperature during sintering and control the cooling rate, thereby relatively easily obtaining alumina-zirconia eutectic ceramics. Simultaneously, it regulates the morphology of alumina and zirconia grains in the eutectic ceramics, achieving optimized and improved properties such as the coefficient of thermal expansion and fracture toughness of the eutectic dense ceramics.

[0027] This invention introduces a certain concentration of yttrium oxide into alumina-zirconia multiphase ceramics, forming an irregular Al2O3 / Y2O3 / ZrO2 ternary eutectic structure in the crystal transition region. Furthermore, yttrium oxide also plays a role in regulating the undercooling during the low-temperature gradient solidification process, thereby altering the morphology of zirconia crystals and thus adjusting the fracture toughness and flexural strength of the alumina-zirconia eutectic ceramics.

[0028] The alumina-zirconia eutectic sintering material prepared by this invention is low in cost and simple to process, making it suitable for large-scale mass production. The alumina-zirconia eutectic sintering material has a density of 92-97%, a microhardness of 16-21 GPa, a flexural strength of 820-980 MPa, a thermal conductivity of 4.0-9.0 W / m·K, and a coefficient of thermal expansion of 7.0-8.5 × 10⁻⁶. -6 / K, fracture toughness is 6.6-8.9 MPa·m 1 / 2 The maximum operating temperature is 1800-2000℃, and the compression creep is 0.01-0.03% under the conditions of 1200℃, 100MPa and heat preservation and pressure holding for 600min.

[0029] The alumina-zirconia eutectic sintering material prepared by this invention has the characteristics of high density, high hardness, high flexural strength, high fracture toughness, and excellent creep performance. The preparation process is simple, and the eutectic structure design can greatly improve the mechanical properties and fracture toughness of the sintering material, which has good application prospects in the fields of high-temperature structural ceramics.

[0030] In summary, compared with traditional technologies, this invention obtains alumina-zirconia eutectic sintering materials through wet grinding of raw material powder, compact preparation, and spark plasma sintering. These eutectic sintering materials have the characteristics of high strength, high fracture toughness, and good creep resistance. The method is simple to operate, environmentally friendly, low in cost, short in process, and highly efficient, which is conducive to large-scale industrial production and promotion. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 Figure 1 shows a microstructure of an alumina-zirconia eutectic sintering material according to Embodiment 1 of the present invention; wherein, Figure a is a microstructure of the eutectic ceramic after sintering, and Figure b is a further magnified microstructure. Detailed Implementation

[0033] The technical solution of the present invention will now be described with reference to the accompanying drawings.

[0034] In embodiments of the present invention, words such as "exemplarily," "for example," etc., are used to indicate that something is an example, illustration, or description. Any embodiment or design described as "exemplary" in the present invention should not be construed as being more preferred or advantageous than other embodiments or designs. Specifically, the use of the word "exemplary" is intended to present the concept in a concrete manner. Furthermore, in embodiments of the present invention, the meaning expressed by "and / or" can be both, or either one.

[0035] In the embodiments of the present invention, the terms "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction is not emphasized, their intended meanings are consistent.

[0036] In this embodiment of the invention, sometimes a subscript such as W1 may be written in a non-subscript form such as W1. When the difference is not emphasized, the meaning they express is the same.

[0037] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0038] An alumina-zirconia eutectic sintering material, comprising 80-95 parts alumina powder, 1-10 parts zirconia powder, 0.1-1 parts yttrium oxide powder, and 2-5 parts binder.

[0039] Specifically, the microstructure of the alumina-zirconia eutectic sintered material is characterized by an alternating arrangement of layered alumina and zirconia grains. Zirconia grains are randomly interspersed within the alumina grains in stripe or cylindrical rod shapes, with a grain thickness <200 nm. The alumina grain size is 100-1000 nm, and the Y₂O₃ grain size is 100-5000 nm. 2 The number of alumina grains per unit area is 100-2000, and the number of zirconia grains is 10-500.

[0040] Specifically, the alumina-zirconia eutectic sintered material has a density of 92-97%, a microhardness of 16-21 GPa, a flexural strength of 820-980 MPa, a thermal conductivity of 4.0-9.0 W / m·K, and a coefficient of thermal expansion of 7.0-8.5 × 10⁻⁶. -6 / K, fracture toughness is 6.6-8.9 MPa·m 1 / 2 The maximum operating temperature is 1800-2000℃, and the compression creep is 0.01-0.03% under the conditions of 1200℃, 100MPa and heat preservation and pressure holding for 600min.

[0041] A method for preparing the alumina-zirconia eutectic sintering material, wherein the preparation method of the alumina-zirconia eutectic sintering material specifically includes the following steps:

[0042] S1. Wet milling of raw material powder: Alumina powder, zirconium oxide powder, and yttrium oxide powder are dispersed in a solvent in the required proportion of alumina-zirconia eutectic sintering material, and then wet milled and dried to obtain mixed powder;

[0043] S2, Preparation of compact: Add binder to the mixed powder of S1 and grind it evenly. After drying, press it into shape to obtain the mixed compact;

[0044] S3, Spark Plasma Sintering: The mixed compact of S3 is subjected to SPS spark plasma sintering to obtain alumina-zirconia eutectic sintering material.

[0045] Specifically, the alumina powder of S1 has a particle size of 0.5-10 μm and a purity of Al2O3≥99wt%; the zirconium oxide powder has a diameter of 1-5 μm and a purity of ZrO2≥99wt%; and the yttrium oxide powder has a diameter of 0.1-0.5 μm and a purity of Y2O3≥99wt%.

[0046] Specifically, the solvent of S1 is one or more of deionized water and anhydrous ethanol, the grinding balls for wet milling are alumina balls, the ball-to-material ratio is 1:2.0-1:3.0, the ball milling speed is 300-400 r / min, the ball milling time is 24-36 h, the drying temperature is 50-110℃, the drying time is 24-36 h, and the average particle size of the mixed powder is 0.1-5 μm.

[0047] Specifically, the binder of S2 is one or more aqueous solutions of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, and carrageenan, and the organic content is 5 wt%.

[0048] Specifically, the grinding media for S2 with added binder is alumina balls, the grinding speed is 300-400 r / min, the drying temperature is 50-110℃, the drying time is 24-36 h, and the molding pressure for pressing is 100-150 MPa.

[0049] Specifically, the pressure on the blank during the SPS discharge plasma heat treatment process of S3 is 5-20kN, the heating rate during sintering is 50-100℃ / min, the cooling rate is 100-200℃ / min, the sintering atmosphere is argon atmosphere, the heat treatment temperature is 1500-1700℃, and the holding time is 2-10min.

[0050] Example 1

[0051] This embodiment provides an alumina-zirconia eutectic sintering material comprising 95 parts alumina powder, 1 part zirconia powder, 0.1 parts yttrium oxide powder, and 2-3 parts binder.

[0052] A method for preparing the alumina-zirconia eutectic sintering material, wherein the preparation method of the alumina-zirconia eutectic sintering material specifically includes the following steps:

[0053] S1. Wet milling of raw material powder: The particle size of alumina powder in the raw material powder is 0.5-10μm, D 50 =3μm, purity Al2O3≥99wt%; zirconium oxide powder diameter is 1-5μm, D 50 =2μm, purity of ZrO2≥99wt%; yttrium oxide powder diameter is 0.1-0.5μm, D 50 =0.2μm, purity Y2O3≥99wt%; alumina powder, zirconium oxide powder, and yttrium oxide powder were dispersed in deionized water in the required proportion for alumina-zirconia eutectic sintering material, and then wet-milled and dried to obtain a mixed powder; the grinding balls used in the wet milling were alumina balls, the ball-to-powder ratio was 1:3.0, the ball milling speed was 400 r / min, the ball milling time was 24 h, the drying temperature was 50℃, the drying time was 24 h, and the average particle size of the mixed powder was 5μm;

[0054] S2. Preparation of compact: Add 5 parts of a 5 wt% (w / w) binder of polyvinyl alcohol and carboxymethyl cellulose aqueous solution to the mixed powder of S1 and grind evenly. The grinding media for adding the binder is alumina balls, and the grinding speed is 300 r / min. The ratio of polyvinyl alcohol to carboxymethyl cellulose is 5:5. After drying, press and shape to obtain a mixed compact. The drying temperature is 80℃, the drying time is 30 min, and the pressing pressure is 100 MPa.

[0055] S3, Spark Plasma Sintering: The mixed compact of S3 is subjected to SPS spark plasma sintering. The pressure on the compact during the SPS spark plasma heat treatment process is 5kN, the heating rate during the sintering process is 50℃ / min, the cooling rate is 100℃ / min, the sintering atmosphere is argon atmosphere, the heat treatment temperature is 1500℃, and the holding time is 2min, to obtain alumina-zirconia eutectic sintering material.

[0056] like Figure 1As shown, the microstructure of the alumina-zirconia eutectic sintered material prepared in this embodiment is characterized by an alternating arrangement of layered alumina and zirconia grains. Zirconia grains are randomly interspersed within the alumina grains in stripe or cylindrical rod shapes, with a grain thickness <200 nm. The average grain size of alumina is 3000 nm, and the average grain size of Y₂O₃ is 100 nm. 2 The average number of alumina grains per unit area is 2000, and the average number of zirconium grains per unit area is 400.

[0057] The alumina-zirconia eutectic sintered material prepared in this embodiment has a density of 92%, a microhardness of 16 GPa, a flexural strength of 820 MPa, a thermal conductivity range of 6.0 W / m·K, and a coefficient of thermal expansion of 7.5 × 10⁻⁶. -6 / K, fracture toughness is 6.6MPa·m 1 / 2 The maximum operating temperature is 1800-1900℃, and the compression creep is 0.03% under the conditions of 1200℃, 100MPa and heat and pressure holding for 600min.

[0058] Example 2

[0059] This embodiment provides an alumina-zirconia eutectic sintering material comprising 80 parts alumina powder, 10 parts zirconia powder, 1 part yttrium oxide powder, and 3-5 parts binder.

[0060] A method for preparing the alumina-zirconia eutectic sintering material, wherein the preparation method of the alumina-zirconia eutectic sintering material specifically includes the following steps:

[0061] S1. Wet milling of raw material powders: The alumina powder has a particle size of 0.5-10 μm and a purity of Al2O3≥99wt%; the zirconium oxide powder has a diameter of 1-5 μm and a purity of ZrO2≥99wt%; the yttrium oxide powder has a diameter of 0.1-0.5 μm and a purity of Y2O3≥99wt%. The alumina powder, zirconium oxide powder, and yttrium oxide powder are dispersed in deionized water in the required proportion for the alumina-zirconia eutectic sintering material. After wet milling and drying, a mixed powder is obtained. The grinding balls used for wet milling are alumina balls, the ball-to-material ratio is 1:2.5, the ball milling speed is 400 r / min, the ball milling time is 36 h, the drying temperature is 110℃, the drying time is 28 h, and the average particle size of the mixed powder is 0.1-3 μm.

[0062] S2. Preparation of compact: Add 6 parts of a 5 wt% (w / w) binder of polyethylene glycol and carboxymethyl cellulose aqueous solution to the mixed powder of S1 and grind evenly. The grinding media for adding the binder is alumina balls, and the grinding speed is 350 r / min. The ratio of polyethylene glycol to carboxymethyl cellulose is 3:7. After drying, press and shape to obtain a mixed compact. The drying temperature is 60℃, the drying time is 30 hh, and the pressing pressure is 150 MPa.

[0063] S3, Spark Plasma Sintering: The mixed compact of S3 is subjected to SPS spark plasma sintering. The pressure on the compact during the SPS spark plasma heat treatment process is 20kN. The heating rate during the sintering process is 100℃ / min, the cooling rate is 200℃ / min, the sintering atmosphere is argon atmosphere, the heat treatment temperature is 1700℃, and the holding time is 10min, to obtain alumina-zirconia eutectic sintering material.

[0064] The microstructure of the alumina-zirconia eutectic sintered material prepared in this embodiment is characterized by an alternating arrangement of layered alumina and zirconia grains. Zirconia grains are randomly interspersed within the alumina grains in stripe or cylindrical rod shapes, with a grain thickness <200 nm. The average grain size of alumina is 100-300 nm, and the average grain size of Y₂O₃ is 100-1000 nm. 2 The average number of alumina grains per unit area is 800-2000, while the average number of zirconium grains per unit area is 200-500.

[0065] The alumina-zirconia eutectic sintered material prepared in this embodiment has a density of 97%, a microhardness of 21 GPa, a flexural strength of 980 MPa, a thermal conductivity range of 6.0-9.0 W / m·K, and a coefficient of thermal expansion of 8.0-8.5 × 10⁻⁶. -6 / K, fracture toughness is 8.9 MPa·m 1 / 2 The maximum operating temperature is 1900-2000℃, and the compression creep is 0.01% under the conditions of 1200℃, 100MPa and heat and pressure holding for 600min.

[0066] Example 3

[0067] This embodiment provides an alumina-zirconia eutectic sintering material comprising 90 parts alumina powder, 5 parts zirconia powder, 0.5 parts yttrium oxide powder, and 3-4 parts binder.

[0068] A method for preparing the alumina-zirconia eutectic sintering material, wherein the preparation method of the alumina-zirconia eutectic sintering material specifically includes the following steps:

[0069] S1. Wet milling of raw material powder: The particle size of alumina powder in the raw material powder is 0.5-10μm, D 50 =3μm, purity Al2O3≥99wt%; zirconium oxide powder diameter is 1-5μm, D 50 =2μm, purity of ZrO2≥99wt%; yttrium oxide powder diameter is 0.1-0.5μm, D 50 =0.2μm, purity Y2O3≥99wt%; alumina powder, zirconium oxide powder, and yttrium oxide powder were dispersed in deionized water in the required proportion for alumina-zirconia eutectic sintering material, and then wet-milled and dried to obtain a mixed powder; the grinding balls used for wet milling were alumina balls, the ball-to-material ratio was 1:2.5, the ball milling speed was 350 r / min, the ball milling time was 30 h, the drying temperature was 70 ℃, the drying time was 30 h, and the average particle size of the mixed powder was 1-4μm;

[0070] S2. Preparation of compact: Add 4 parts of a 5 wt% polyvinyl alcohol and lacquer aqueous solution as a binder to the mixed powder of S1 and grind it evenly. The grinding media for adding the binder is alumina balls, and the grinding speed is 350 r / min. The ratio of polyvinyl alcohol to lacquer is 6:4. After drying, press it into a mixed compact. The drying temperature is 80℃, the drying time is 30 h, and the pressing pressure is 120 MPa.

[0071] S3, Spark Plasma Sintering: The mixed compact of S3 is subjected to SPS spark plasma sintering. The pressure on the compact during the SPS spark plasma heat treatment process is 12kN. The heating rate during the sintering process is 70℃ / min, the cooling rate is 150℃ / min, the sintering atmosphere is argon atmosphere, the heat treatment temperature is 1600℃, and the holding time is 6min, to obtain alumina-zirconia eutectic sintering material.

[0072] The microstructure of the alumina-zirconia eutectic sintered material prepared in this embodiment is characterized by an alternating arrangement of layered alumina and zirconia grains. Zirconia grains are randomly interspersed within the alumina grains in stripe or cylindrical rod shapes, with a grain thickness <200 nm. The average grain size of alumina is 300-700 nm, and the average grain size of Y₂O₃ is 2000-4000 nm. (100 μm) 2 The average number of alumina grains per unit area is 200-1000, while the average number of zirconium grains per unit area is 150-400.

[0073] The alumina-zirconia eutectic sintered material prepared in this embodiment has a density of 95%, a microhardness of 20 GPa, a flexural strength of 920 MPa, a thermal conductivity range of 6.0-8.0 W / m·K, and a coefficient of thermal expansion of 7.5-8.0 × 10⁻⁶. -6 / K, fracture toughness is 7.5MPa·m 1 / 2 The maximum operating temperature is 1800-1900℃, and the compression creep is 0.02% under the conditions of 1200℃, 100MPa and heat and pressure holding for 600min.

[0074] The above-mentioned solution proposes an alumina-zirconia eutectic sintering material and its preparation method, which can solve the technical problems existing in the preparation of alumina-zirconia composite ceramic materials, such as the deterioration of high-temperature creep performance due to the addition of various sintering aids, the random distribution of zirconia phase without effective crystal structure distribution design, the insignificant toughening effect, the low flexural strength of composite ceramic materials, low efficiency, high cost, and unsuitability for large-scale industrial production.

[0075] This invention employs spark plasma sintering technology to rapidly raise the temperature to the target temperature during sintering and control the cooling rate, which can relatively easily obtain alumina-zirconia eutectic ceramics. At the same time, it can regulate the morphology of alumina and zirconia grains in the eutectic ceramics to optimize and improve the thermal expansion coefficient, fracture toughness and other properties of the eutectic dense ceramics.

[0076] This invention introduces a certain concentration of yttrium oxide into an alumina-zirconia multiphase ceramic, thereby forming irregular Al2O3 / Y3Al5O3 crystals in the transition region of the crystal clusters. 12 The formation of the ZrO2 ternary eutectic structure, and the role of yttrium oxide in regulating the undercooling during the low-temperature gradient solidification process, changes the morphology of zirconium oxide crystals, thereby regulating the fracture toughness and flexural strength of alumina-zirconia eutectic ceramics.

[0077] The alumina-zirconia eutectic sintering material prepared by this invention is low in cost and simple to process, making it suitable for large-scale mass production. The alumina-zirconia eutectic sintering material has a density of 92-97%, a microhardness of 16-21 GPa, a flexural strength of 820-980 MPa, a thermal conductivity of 4.0-9.0 W / m·K, and a coefficient of thermal expansion of 7.0-8.5 × 10⁻⁶. -6 / K, fracture toughness is 6.6-8.9 MPa·m 1 / 2 The maximum operating temperature is 1800-2000℃, and the compression creep is 0.01-0.03% under the conditions of 1200℃, 100MPa and heat preservation and pressure holding for 600min.

[0078] The alumina-zirconia eutectic sintering material prepared by this invention has the characteristics of high density, high hardness, high flexural strength, high fracture toughness, and excellent creep performance. The preparation process is simple, and the eutectic structure design can greatly improve the mechanical properties and fracture toughness of the sintering material, which has good application prospects in the fields of high-temperature structural ceramics.

[0079] In summary, compared with traditional technologies, this invention obtains alumina-zirconia eutectic sintering materials through wet grinding of raw material powder, compact preparation, and spark plasma sintering. These eutectic sintering materials have the characteristics of high strength, high fracture toughness, and good creep resistance. The method is simple to operate, environmentally friendly, low in cost, short in process, and highly efficient, which is conducive to large-scale industrial production and promotion.

[0080] It should be understood that the term "and / or" in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. Additionally, the character " / " in this article generally indicates an "or" relationship between the preceding and following related objects, but it can also represent an "and / or" relationship. Please refer to the context for a more accurate understanding.

[0081] In this invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of a single item or a plurality of items. For example, at least one of a, b, or c can represent: a, b, c, ab, ac, bc, or abc, where a, b, and c can be a single item or multiple items.

[0082] It should be understood that, in various embodiments of the present invention, the order of the above-mentioned process numbers does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0083] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.

Claims

1. An alumina-zirconia eutectic sintering material, characterized in that, The alumina-zirconia eutectic sintering material comprises 80-95 parts alumina powder, 1-10 parts zirconia powder, 0.1-1 parts yttrium oxide powder, and 2-5 parts binder.

2. The alumina-zirconia eutectic sintering material according to claim 1, characterized in that, The microstructure of the alumina-zirconia eutectic sintered material is characterized by alternating layers of alumina and zirconia grains. Zirconia grains are randomly interspersed within the alumina grains in stripe or cylindrical rod shapes, with a grain thickness <200 nm. The alumina grain size is 100-1000 nm, and the Y₂O₃ grain size is 200-2000 nm. (100 μm) 2 The number of alumina grains per unit area is 100-2000, and the number of zirconia grains is 10-500.

3. The alumina-zirconia eutectic sintering material according to claim 1, characterized in that, The alumina-zirconia eutectic sintered material has a density of 92-97%, a microhardness of 16-21 GPa, a flexural strength of 820-980 MPa, a thermal conductivity of 4.0-9.0 W / m·K, and a coefficient of thermal expansion of 7.0-8.5 × 10⁻⁶. -6 / K, fracture toughness is 6.6-8.9 MPa·m 1 / 2 The maximum operating temperature is 1800-2000℃, and the compression creep is 0.01-0.03% under the conditions of 1200℃, 100MPa and heat preservation and pressure holding for 600min.

4. A method for preparing the alumina-zirconia eutectic sintering material according to any one of claims 1-3, characterized in that, The specific steps for preparing the alumina-zirconia eutectic sintering material are as follows: S1. Wet milling of raw material powder: Alumina powder, zirconium oxide powder, and yttrium oxide powder are dispersed in a solvent in the required proportion of alumina-zirconia eutectic sintering material, and then wet milled and dried to obtain mixed powder; S2, Preparation of compact: Add binder to the mixed powder of S1 and grind it evenly. After drying, press it into shape to obtain the mixed compact; S3, Spark Plasma Sintering: The mixed compact of S3 is subjected to SPS spark plasma sintering to obtain alumina-zirconia eutectic sintering material.

5. The method for preparing the alumina-zirconia eutectic sintering material according to claim 4, characterized in that, The alumina powder of S1 has a particle size of 0.5-10 μm and a purity of Al2O3≥99wt%; the zirconium oxide powder has a diameter of 1-5 μm and a purity of ZrO2≥99wt%; and the yttrium oxide powder has a diameter of 0.1-0.5 μm and a purity of Y2O3≥99wt%.

6. The method for preparing the alumina-zirconia eutectic sintering material according to claim 4, characterized in that, The solvent for S1 is one or more of deionized water and anhydrous ethanol. The ball milling media for wet milling is alumina balls, the ball-to-material ratio is 1:2-1:3, the ball milling speed is 300-400 r / min, the ball milling time is 12-24 h, the drying temperature is 50-110 ℃, the drying time is 24-36 h, and the average particle size of the mixed powder is 0.1-5 μm.

7. The method for preparing the alumina-zirconia eutectic sintering material according to claim 4, characterized in that, The binder of S2 is one or more aqueous solutions of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose, and carrageenan, and the organic content is 5 wt%.

8. The method for preparing the alumina-zirconia eutectic sintering material according to claim 4, characterized in that, The S2 binder uses alumina balls as the grinding medium, with a grinding speed of 300-400 r / min, a drying temperature of 50-110℃, a drying time of 24-36 h, and a pressing pressure of 100-150 MPa.

9. The method for preparing the alumina-zirconia eutectic sintering material according to claim 4, characterized in that, The pressure on the blank during the SPS discharge plasma heat treatment process of S3 is 5-20kN, the heating rate during sintering is 50-100℃ / min, the cooling rate is 100-200℃ / min, the sintering atmosphere is argon atmosphere, the heat treatment temperature is 1500-1700℃, and the holding time is 2-10min.

Citation Information

Patent Citations

  • Alumina / alumina-zirconia laminar composite with composite structure and preparation method thereof

    CN103072325A

  • Method for preparing micro-nano zirconia / aluminium oxide composite material

    CN106518028A

  • Preparation method of zirconium oxide toughened aluminum oxide powder and ceramic

    CN112456979A

  • Preparation method of high-strength 96 aluminum oxide ceramic

    CN115536371A

  • Preparation method of high-hardness alumina-zirconia composite ceramic

    CN118515471A

Cited By

  • Rare earth co-doped high-toughness alumina-based ceramic ball and preparation method thereof

    CN122059689A